POLITICAL MARRIAGE REFLECTED IN MIQUEL SAPOCHNIK’S HOUSE OF THE DRAGON (2022) - Najih, Irfin; Widiyanti, Ana (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This descriptive qualitative research aims to examine how The House of Dragon Movie represent complex issues in political marriage practice. By using sociological theory and close textual analysis, this research examines how the movie presents political practice and how the effect of patriarchal system in political marriage over women’s life. The film is indeed portrayed the condition of people, especially the ones who belong to high classes or powerful society in confronting political marriage. The research finding shows that political marriage is a common practice in classical era, especially in royal or high classes family, to secure their belonging, status, or power. The others finding are: 1) political marriage is usually set since the children of royal family or high classes society are still child; 2) patriarchal system often become the most influence to make political marriage practice happen; 3) political marriage under the effect of patriarchal system brings hardship for women in many aspects of life.